Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve the given function [tex]\( f(x) = x^3 - 3x^2 + 4x - 12 \)[/tex] and evaluate it at [tex]\( x = 3 \)[/tex].
### Step-by-Step Solution:
1. Identify the function and the value of [tex]\( x \)[/tex]:
- We are given the function [tex]\( f(x) = x^3 - 3x^2 + 4x - 12 \)[/tex].
- We are also given the value [tex]\( x = 3 \)[/tex].
2. Substitute [tex]\( x = 3 \)[/tex] into the function:
- Replace every occurrence of [tex]\( x \)[/tex] in the function [tex]\( f(x) \)[/tex] with [tex]\( 3 \)[/tex].
So we get:
[tex]\[ f(3) = 3^3 - 3(3^2) + 4(3) - 12 \][/tex]
3. Calculate each term step-by-step:
- First term: [tex]\( 3^3 = 27 \)[/tex]
- Second term: [tex]\( -3(3^2) = -3(9) = -27 \)[/tex]
- Third term: [tex]\( 4(3) = 12 \)[/tex]
- Fourth term: [tex]\( -12 \)[/tex]
4. Combine the results:
- Now, add and subtract these results step-by-step:
[tex]\[ f(3) = 27 - 27 + 12 - 12 \][/tex]
5. Simplify the expression:
- Combining the terms, we get:
[tex]\[ 27 - 27 = 0 \][/tex]
- Next, combine:
[tex]\[ 12 - 12 = 0 \][/tex]
- Finally:
[tex]\[ 0 + 0 = 0 \][/tex]
### Final Answer:
[tex]\[ f(3) = 0 \][/tex]
So, when [tex]\( x = 3 \)[/tex], the value of the function [tex]\( f(x) = x^3 - 3x^2 + 4x - 12 \)[/tex] is [tex]\( 0 \)[/tex].
### Step-by-Step Solution:
1. Identify the function and the value of [tex]\( x \)[/tex]:
- We are given the function [tex]\( f(x) = x^3 - 3x^2 + 4x - 12 \)[/tex].
- We are also given the value [tex]\( x = 3 \)[/tex].
2. Substitute [tex]\( x = 3 \)[/tex] into the function:
- Replace every occurrence of [tex]\( x \)[/tex] in the function [tex]\( f(x) \)[/tex] with [tex]\( 3 \)[/tex].
So we get:
[tex]\[ f(3) = 3^3 - 3(3^2) + 4(3) - 12 \][/tex]
3. Calculate each term step-by-step:
- First term: [tex]\( 3^3 = 27 \)[/tex]
- Second term: [tex]\( -3(3^2) = -3(9) = -27 \)[/tex]
- Third term: [tex]\( 4(3) = 12 \)[/tex]
- Fourth term: [tex]\( -12 \)[/tex]
4. Combine the results:
- Now, add and subtract these results step-by-step:
[tex]\[ f(3) = 27 - 27 + 12 - 12 \][/tex]
5. Simplify the expression:
- Combining the terms, we get:
[tex]\[ 27 - 27 = 0 \][/tex]
- Next, combine:
[tex]\[ 12 - 12 = 0 \][/tex]
- Finally:
[tex]\[ 0 + 0 = 0 \][/tex]
### Final Answer:
[tex]\[ f(3) = 0 \][/tex]
So, when [tex]\( x = 3 \)[/tex], the value of the function [tex]\( f(x) = x^3 - 3x^2 + 4x - 12 \)[/tex] is [tex]\( 0 \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.